Informal logic in Islamic theology: Argumentative study of the inferential structure theological debate - Khabbah, Hind (Journal of Humanities & Social Sciences, 2022)
Informal logic aims to study arguments formulated in natural language, examine their inferential structure, and extrapolate general criteria that enable us to judge the invalidity of an argument or vice versa. It transcends its limit, which is confined to the infallibility of thought from error, and transcends it to work to overthrow false arguments.Therefore, we decided to reveal this kind of logic through the argumentative theory, which gives the possibility to evoke the domicile and contextual dimension of the subject of the argumentative process, and to highlight the role played by the Ethos, Pathos, Logos, enthymeme, and the introspection of implicit forms in the discourse, and taking into account the psychological and sociological dimensions. and the ideological background, and for this reason, one of the endeavors of this study is to analyze the inferential structure of Islamic theological discourse with analogous denominators, in which the pilgrims relied on the creed. To illustrate this, the "Al-Aslah wa Salaah" debate, which took place between "Al-Jabai" and "Al-Ash'ari", was chosen. by adopting a method that combines analysis and conclusion, imposed by the nature of the subject, which was among the reasons for choosing the intellectual and ideological conflict, which in a large part has become subject to purely political orientations, predicting ideological transformations of a significant degree of danger that seek to crush the constants, and to blind the insights through fallacies. Logical and dissemination on a large scale, so one of the most prominent recommendations that this study urges is to be able to use arguments and logical mechanisms to distinguish between right and wrong and protect oneself from being drawn into arguments that are formed in false and fragile logical images.
Keywords: loose/non-formal logic; theology; argumentative theory; debate